Pengaruh Proporsi Daging Ikan Patin (Pangasius hypophthalmus) dan Wortel (Daucus carota L) Terhadap Kadar Protein, Kalsium dan Daya Terima Stik Nugget Ikan - Yuliana Salaman; Sari Novita; Nor Raisa Shaliha; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
South Borneo has abundant aquatic product, one of the commodities are Patin fish (Pangasius hypophthalmus). Patin is a species of fish that have high protein content. Besides Patin fish, carrots also one horticultural commodity are derived from vegetable group which has high calcium content. Food diversification is essential in order to increase the diversity of food in Indonesia. Diversification can be done using patin fish that added with carrot on making fish nugget stick. This research was to know effect of proportion Patin fish (Pangasius hypophthalmus) and carrot (Daucus carato L) toward protein and calcium level and the acceptance of fish nugget sticks. This research is experimental. This study is an experiment, using a completely randomized design, with 4 treatments and 3 replications with each treatment that P0(100: 0), P1 treatment(95: 5) P2 treatment (90: 10) and P3 treatment (85: 15).The research design used was a completely randomized design. Test methods for protein content by Kjedhal method and calcium with Titrimitri method. Organoleptic testing method with the hedonic method (acceptance test). Organoleptic statistic test using Friedman test. Statistical test for levels of protein and calcium is One Way ANOVA. If there isany influence of different test methods tukey The results showed no effect proportion Patin fish and carrot toward protein levels of fish nugget sticks (p = 0,449). There is effect proportion Patin fish and carrot against calcium levels of fish nugget sticks (p = 0,001). There is no effect between proportion Patin fish and carrot against the acceptance of fish nugget sticks for color (p = 0,050), scent (p = 0,836), flavor (p = 0,979), whereas texture no effect on the acceptance (P = 0,047). The best treatment in terms of the acceptance (color, texture, flavor) i.e. P3 treatment, then best treatment for protein levels i.e. P1 treatment with an average value of 23,33% and the best treatment of calcium levels i.e. P3 treatment with average value of 9,5%.